DOCK 8 Deficiency, EBV+ Lymphomatoid Granulomatosis, and Intrafamilial Variation in Presentation - Dimitriades, Victoria R.; Devlin, Vincent; Pittaluga, Stefania; Su, Helen C.; Holland, Steven M.; Wilson, Wyndham; Dunleavy, Kieron; Shah, Nirali N.; Freeman, Alexandra F. (Frontiers in Pediatrics, 2017)
Dedicator of cytokinesis 8 (DOCK8) deficiency is an autosomal recessive, combined immunodeficiency within the spectrum of hyper-IgE syndromes (HIES). Epstein-Barr Virus-positive lymphomatoid granulomatosis (EBV+LYG) is a rare diagnosis and a previously unreported presentation of DOCK8 deficiency. A 10-year-old girl was initially evaluated for mild eczema and recurrent sinopulmonary infections. She had normal immunoglobulins with elevated IgE, poor polysaccharide response with low switched memory B cells, low CD4 count, and normal mitogen and antigen responses. Despite clinical improvement following immunoglobulin replacement, a prolonged cough prompted a CT scan, which showed nodules. Biopsy identified a Grade 2 EBV+ LYG . Due to an inadequate response with chemotherapy, further work-up for primary immunodeficiency was performed. With her symptoms of eczema and IgE elevation, along with her brother’s history of recurrent sinopulmonary infections and warts, targeted sequencing of DOCK8 was performed revealing compound heterozygous mutations for the two siblings. Both patients were successfully transplanted with resolution of the LYG and warts, respectively. This is the first reported case of LYG in DOCK8 deficiency. The EBV-driven lymphoproliferative disease along with the infection history in the brother led to the diagnosis of DOCK8 deficiency and curative hematopoietic stem cell transplants.